Kurangnya Minat Baca Anak Generasi Alpha Di Era Perkembangan Teknologi - Muhamad Haykal Muttaqin; Adam Andreansyah; Reza Mauldy Raharja (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
The alpha generation is the children that the millenial generation has left behind. This article was written by Mark Mc Crindle and published in the Business Insider magazine (Christina Sterbenz, 2015). The Alpha Generation (2011–2025) is the most advanced generation in terms of digital technology and the least advanced generation in comparison to the previous generation. Every day, almost 2.5 million children of the Alpha Generation are born into the world. The generation most familiar with the internet over the long term is Gen A. Mc Crindler also asserts that the Alpha generation is not averse to technology, somewhat socially adept, somewhat creative, and somewhat independent. Alpha generators require quick and somewhat chaotic processes. By enticing them with a technology, they become socially alienated. This article aims to understand the challenges faced by the Alpha Generation in the Industrial Revolution. For many people, literacy is a familiar language. Literasi is a concept with a complex, dynamic, and ever-changing definition that is defined by several methods with extreme caution. According Keywords: Literacy, Technology, Development, and Generation Alpha. to an online Merriam-Webster dictionary, the words "literature" and "letter" come from the Latin and English languages, respectively. Literasi is quality, or the ability to read and write with huruf/aksara that is included in the text. Technology is described as a concept that has to do with the type of application and knowledge about how it might improve human ability to identify and modify objects that are around. At this point in time, technological advancement is experiencing relatively slow advancement. The idea of technological advancement is to advance technology from one era to the next, making it more advanced or better. The ability of the Alpha generation to communicate (read, write, study, and sketch) has somewhat declined as a result of the rapid advancement of technology. Many Alpha children nowadays are highly dependent on their gadgets (games, YouTube videos, and other apps). However, due to technological developments, alpha generation children are lagging behind in literature, which is why they are interested in reading at an age when they should be able to read and understand the content of what they read.